A Literary Psychological Analysis of the Main Characters in the Film Dunia Tanpa Suara by Hanung Bramantyo - Fitri Aulia Haliza; Abdul Malik; Ahada Wahyusari; Isnaini Leo Shanty; Dody Irawan; Tessa Dwi Leoni (Jurnal Pembelajaran Bahasa dan Sastra, 2026)
This study aims to describe the personality structure of the main character Arissa in the film Dunia Tanpa Suara by Hanung Bramantyo using Sigmund Freud’s psychoanalytic theory which includes the aspects of id, ego, and superego. The method used in this study is descriptive qualitative with a literary psychology approach. The instrument in this study is the researcher herself who acts as the planner, implementer, data collector, and data analyzer of the research. The data collection technique in this study is the observation and note-taking technique which is carried out repeatedly to obtain data relevant to the focus of the study. The data analysis technique in this study is carried out by systematic data reduction, data presentation, and drawing conclusions based on the theoretical concepts used. The results of the study show that (1) the id aspect is seen through Arissa’s instinctive urge to fulfill needs, vent emotions spontaneously, and avoid discomfort without much consideration; (2) the ego aspect is seen when Arissa considers reality before acting, adapts to social situations, and makes logical decisions based on real conditions; and (3) the superego aspect is reflected in Arissa’s attitude of adhering to moral values, showing guilt after violating norms, and refusing to carry out actions that are contrary to ethics even though they can benefit her. The findings of this study indicate that the personality structure of the main character is formed through the interaction between instinctive drives, real conditions, and moral control.